Laparoscopic Cytoreductive Surgery and HIPEC in Patients with Limited Pseudomyxoma Peritonei of Appendiceal Origin - Jesus Esquivel; Andrew Averbach (Gastroenterology Research and Practice)
Introduction. Increasing numbers of patients with pseudomyxoma peritonei (PMP) of appendiceal origin are being evaluated with a low tumor burden. We explored a minimally invasive approach for this group of patients. Materials and Methods. We designed a protocol in which patients with a PMP diagnosis would have a diagnostic laparoscopy. If limited carcinomatosis (PCI ≤ 10) is identified, the procedure will continue laparoscopically. If extensive carcinomatosis (PCI > 10) is found, then the procedure will be converted to an open approach. Results. From December 2008 to December 2011, 19 patients had a complete cytoreduction and HIPEC: 18 of them (95%) were done laparoscopically and 1 of them (5%) was converted to an open procedure. Mean PCI was 4.2. Grade 3 morbidity was 0, and one patient (5%) experienced a grade 4 complication, needing a reoperation for an internal hernia. There were no mortalities. Mean length of hospital stay was 5.3 days. At a mean follow-up of 17 months (1–37) all 19 patients are alive and free of disease. Conclusion. This study demonstrates that cytoreductive surgery and HIPEC via the laparoscopic route is feasible and safe and should be offered to patients with limited pseudomyxoma peritonei of appendiceal origin.